Implementasi Humanisme Religius dalam Pembelajaran Pendidikan Islam di Pondok Pesantren MBS Al Amin Bojonegoro - Ibnu Habibi (Proceedings of Annual Conference for Muslim Scholars, 2018)
This research entitled "Implementation of Religious Humanism in Islamic Education Learning at Pondok Pesantren Muhammadiyah Boarding School (MBS) Al Amin Bojonegoro" aims to How the implementation of religious humanism in learning Islamic education in SBM PP Al Amin Bojonegoro, how the inhibiting factors and supporters, and how efforts overcoming the obstacles of the implementation of religious humanism in learning Islamic education in the cottage. The type of this research is descriptive qualitative with research approach used is philosophical, psychological, and pedagogic approach. The data source of this research consist of Leader of Pesantren, Principal, student, builder of Dormitory, teacher and student / santri. Furthermore, data collection methods used are observation, interviews, and documentation. The results of research show that the implementation of religious humanism has been run in accordance with the existing procedures, namely teachers and supervisors menghawannan dignified interaction, learning models (interactive, creative, innovative, active, and fun.At the inhibiting factors and its supporters are external factors include the environment pesantren, supervision of pesantren supervisors, and supervision of parents / guardians, and internal factors include self-control, psychology, and habits while overcoming obstacles to the implementation of religious humanism in learning Islamic education namely Counseling Guidance (BK), Habituation, supervision, and reward and punishment.